Le travail sur soi et à propos de soi à l’occasion d’un récit d'expérience : convocation de différents espaces d’activités - Martine Dutoit (Éducation et Socialisation)
This article reports an ethnographical approach to understand the processes leading to the writing of a book telling an experience lived on confrontation, during almost twenty years, to the psychiatric institution. The author explore how the real-life experience of the initial experience is put back to the work and how the putting in narrative works as an exercise of construction of sense for one in a presentation of one in others. The concept of space of activity is summoned to analyze this work of investigation leading to the writing. Because they are imbricated these various spaces of activity are perceived as the flow of the life itself, always in tension, sometimes concerning the transformation processes of the current activity, sometimes concerning the transformation processes of transformations of the subjects in the course of the activity.